Sedimentología y estratigrafía de alta resolución del subgrupo río Neuquén (Cretácico Superior) departamento confluencia, provincia de Neuquén, Argentina - Sanchez, Maria Lidia (2014)
The Upper Cretaceous exposid in the northeastern part of the Neuquén Basin, southeast of Neuquén, Argentina. Río Neuquén Subgroup of continental origin, has been divided into two incomplete stratigraphic sequence units (SI y SII) on the basis of lithofacies assemblages and architectural elements. Parts of the succession (Portezuelo Formation SI) formed in northeasward-draining low and high sinuosity fluvial systems. Those are analyzed in detail in terms of macroformscale and stratigraphic-level architecture to assess fluvial styles and the evolution of non-marine depositional environments. Lateral and oblique accretion is a significant process of deposition in high-energy systems with mixed load. The overbank deposits dominate the floodplain stratigraphy; they contribute more than 45% of floodplain sediments. The Plottier Formation (SII) was accumulated from a low sinuosity perennial system with well developed deposits of alluvial plain with flood events. The unit was accumulated on topographic slopes dipping from west-southwest to east-northeast. The alluvial architecture and stacking patterns in the Río Neuquén Subgroup were controlled by a combination of allogenic factors, most significantly tectonics followed by climate. The Upper Cretaceous succession in the Andean foreland basin, deposited in a backbulge zone, consists of tectonically-driven cycles comprising two components: strata deposited in an underfilled basin (Portezuelo Formation, AA-SI) and strata deposited in an overfilled basin lacking evidence of a forebulge (Plottier Formation, BA-SII).